FinTech as Moral Governance in Islamic Boarding Schools: Evidence from Digital Pocket Money Management among Santri - Taufikin Taufikin; Muhammad Shobirin; Muhammad Mujahwirul Ilma; Irma Noviana (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The objective of this study is to examine the effectiveness of digital student allowance cards in strengthening financial discipline and transparency in Islamic boarding schools. Financial management in Islamic boarding schools has traditionally relied on cash-based systems that are difficult to monitor and prone to inefficiency. This practice creates a mismatch between character education goals and students’ everyday financial behavior. This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. Data were collected from 50 students through structured questionnaires measuring financial discipline, expenditure control, perceptions of transparency, and monitoring awareness, and analyzed using descriptive statistics and paired difference tests. The findings reveal a significant improvement in students’ financial discipline after the implementation of digital allowance cards. Students demonstrated reduced impulsive spending and greater awareness of spending limits. The system also enhanced students’ ability to plan expenditures more responsibly. In addition, perceptions of transparency and accountability in financial management increased substantially. Monitoring awareness improved as students became more conscious of recorded transactions. These results suggest that digital allowance cards function not merely as administrative instruments but as mechanisms of behavioral regulation. This study contributes to the literature by positioning digital financial systems as tools of moral governance in Islamic education. It recommends that Islamic boarding schools and policymakers integrate technology-based financial systems aligned with the values of character education.